Chronic delivery of α-melanocyte-stimulating hormone in rat hypothalamus using albumin-alginate microparticles: Effects on food intake and body weight. (2nd April 2015) - Lucas, N.; Legrand, R.; Breton, J.; Déchelotte, P.; Edwards-Lévy, F.; Fetissov, S.O.
Highlights: Drug delivery systems to the brain can be useful for experimental and clinical applications. We validated the use of albumin-alginate microparticles as a neuropeptide delivery system. Delivery of α-MSH in the rat hypothalamus decreased food intake and body weight gain. Abstract: Chronic delivery of neuropeptides in the brain is a useful experimental approach to study their long-term effects on various biological parameters. In this work, we tested albumin-alginate microparticles, as a potential delivery system, to study if continuous release in the hypothalamus of α-melanocyte-stimulating hormone (α-MSH), an anorexigenic neuropeptide, may result in a long-term decrease in food intake and body weight. The 2-week release of α-MSH from peptide-loaded particles was confirmed by an in vitro assay. Then, daily food intake and body weight were studied for 18 days in rats injected bilaterally into the paraventricular hypothalamic nucleus with particles loaded or not with α-MSH. A decrease in body weight gain, persisting throughout the study, was found in rats injected with α-MSH-charged particles as compared with rats receiving non-charged particles and with rats injected with the same dose of α-MSH in solution. Food intake was significantly decreased for 3 days in rats receiving α-MSH-loaded particles and it was not followed by the feeding rebound effect which appears after food restriction. The presence of α-MSH-loaded particles in the hypothalamus was confirmed by immunohistochemistry. In conclusion, our study validates albumin-alginate microparticles as a new carrier system for long-term delivery of neuropeptides in the brain and demonstrates that chronic delivery of α-MSH in the hypothalamus results in a prolonged suppression of food intake and a decrease of body weight gain in rats.